ANALISIS KETERAMPILAN KOMUNIKASI INTERPERSONAL PADA SISWA KELAS XI SMA NEGERI 6 PONTIANAK - Khotif, Muhammad; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study contains an analysis of interpersonal communication skills in students Class XI Negeri 6 Pontianak. Academic Year 2018/2019. Deep problems This research is (1) How is the openness of students' interpersonal communication Class XI Negeri 6 Pontianak? (2) How is empathy for interpersonal communication the eleventh grade students of Pontianak 6 Public Middle School? (3) What is the attitude support interpersonal communication Class XI Negeri 6 Pontianak Students? (4) How is the positive attitude of interpersonal communication in eleventh grade students at Pontianak 6 Public High School? (5) How about equality of interpersonal communication Class XI students in Pontianak 6 Public High School? This research uses the method descriptive in the form of a survey. The research subjects were 51 eleventh grade students. Indirect communication and Questionnaire are used as techniques and tools data collection. Technical analysis uses percentages. Based on, students in eleventh grade in SMA Negeri 6 Pontianak reached 82% of Interpersonal Communication and was categorized as "high" interpersonal skills. Based on the description above, in general it can be seen that interpersonal communication made by students of class Xi Of Sma Negeri 6 Pontianak is quite high.Â Keywords: Communication, Interpersonal Skills